Printing pressures: production and circulation of popular literature (Valencia, 18th century) - Ulla Lorenzo, Alejandra (Bulletin of Spanish Studies, 2018)
Reseña de "Printing pressures: production and circulation of popular literature (Valencia, 18th century)" por Alejandara Ulla Lorenzo.
Keywords: reseña; WOS